2015
DOI: 10.1002/lno.10060
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization changes the composition and bioavailability of dissolved organic matter in headwater streams

Abstract: Population growth in cities has resulted in the rapid expansion of urbanized land. Most research and management of stream ecosystems affected by urban expansion has focused on the maintenance and restoration of biotic communities rather than their basal resources. We examined the potential for urbanization to induce bottom-up ecosystem effects by looking at its influence on dissolved organic matter (DOM) composition and bioavailability and microbial enzyme activity. We selected 113 headwater streams across a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
93
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(105 citation statements)
references
References 55 publications
10
93
2
Order By: Relevance
“…In contrast to the lacking or weak correlations indicative of anaerobic CH 4 production in the impounded middle reach, CH 4 measurements in the lower reach exhibited significant negative (DO) or positive (water temperature, C1/DOC, and C2/DOC) correlations related to anaerobic metabolism. As observed in other urbanized river systems (Beaulieu et al, 2015;Smith et al, 2015;Wang 375 et al, 2018), eutrophication (indicated by significant positive correlation with PO 4 3− ), together with lowered DO, might create favourable conditions for anaerobic methanogenesis in the lower reach almost impounded by two submerged weirs. Out of many water quality components that were significantly correlated with N 2 O (Fig.…”
Section: Spatial Variations In Three Ghgs Observed Along the Middle Rmentioning
confidence: 55%
See 1 more Smart Citation
“…In contrast to the lacking or weak correlations indicative of anaerobic CH 4 production in the impounded middle reach, CH 4 measurements in the lower reach exhibited significant negative (DO) or positive (water temperature, C1/DOC, and C2/DOC) correlations related to anaerobic metabolism. As observed in other urbanized river systems (Beaulieu et al, 2015;Smith et al, 2015;Wang 375 et al, 2018), eutrophication (indicated by significant positive correlation with PO 4 3− ), together with lowered DO, might create favourable conditions for anaerobic methanogenesis in the lower reach almost impounded by two submerged weirs. Out of many water quality components that were significantly correlated with N 2 O (Fig.…”
Section: Spatial Variations In Three Ghgs Observed Along the Middle Rmentioning
confidence: 55%
“…and C2/DOC (Fig. 4), which may be associated with terrestrial DOM components and their microbial transformation products (Fellman et al, 2010;Parr et al, 2015). It is likely that the narrow ranges of pCO 2 and Chl a did not result in any significant correlation.…”
Section: Spatial Variations In Three Ghgs Observed Along the Middle Rmentioning
confidence: 99%
“…More specifically, human disturbance commonly alters fluvial OM toward a more microbial/algal and less plant/soil-derived character. This pattern was first observed for DOM (Cronan et al 1999;Giling et al 2014;Graeber et al 2012;Hosen et al 2014;Masese et al 2016;Parr et al 2015;Williams et al 2010Williams et al , 2016Wilson and Xenopoulos 2009;Yang et al 2012), and recently extended to POM (Boëchat et al 2014;Duan et al 2014;Le Meur et al 2017;Lu et al 2014a, b;Ngugi et al 2016).…”
Section: Introductionmentioning
confidence: 69%
“…Terrestrial inputs as well as autochthonous primary production of OM are the result of the interplay of several catchment attributes such as soil properties (Autio et al 2016;Nelson et al 1992), land cover (Giling et al 2014;Wilson and Xenopoulos 2009), hydrology and water residence time (Lambert et al 2014;Sanderman et al 2009) and nutrient availability (Reche et al 1998), all of these basic drivers being altered by human activities (Carpenter et al 2011;Stanley et al 2012). The conversion of natural landscapes for human use has thus been shown to alter the sources, composition and reactivity of fluvial OM with significant effects on carbon cycling in freshwaters (Parr et al 2015;Petrone et al 2011;Rosemond et al 2015;Wilson and Xenopoulos 2009). Our ability to predict future changes in fluvial OM and associated ecological consequences in response to increasing anthropogenic pressures is however hampered by our limited understanding of the processes involved as well as by the fact that DOM and POM fractions are often investigated separately rather than simultaneously.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation